A Case of Ignatzschineria indica Bacteremia following Maggot Colonization - Hugh Muse; Rachel L. Jenkins; Meredith B. Oliver; Soomin Kim; Richard L. Grantier; Bharat K. Malhotra; Jason J. Parham; Kayla R. Stover (Case Reports in Infectious Diseases)
Ignatzschineria indica is a Gram-negative bacterium that is commonly associated with the larvae of flesh flies. I. indica is difficult to isolate in routine laboratory procedures but has been associated with neglected wounds infested with maggots, fever, elevated white blood count and C-reactive protein, and polymicrobial culture results. Other specific hematological/immunological changes are not known. We present a case of I. indica bacteremia and polymicrobial osteomyelitis resulting from infected decubitus ulcers. The patient improved after treatment with cefepime followed by levofloxacin.